Development and effects of a psychosocial adaptation program for North Korean adolescent defectors - In-Sook Lee (Korean Academy of Child Health Nursing, 2021)
Purpose This study aimed to develop and examine the effects of a psychosocial adaptation program for North Korean adolescent defectors. Methods This quasi-experimental study was conducted with 28 North Korean adolescent defectors who were recruited through alternative schools. The experimental and control groups consisted of 14 participants each. A program was conducted across eight sessions, each lasting about 90-120 minutes. The data were analyzed using the x2 test, t-test, paired t-test, and analysis of covariance. Results No significant differences were observed in the score changes for psychosocial adaptation (t=0.25, p=.808), post-traumatic stress symptoms (t=0.32, p=.749), cultural adaptation stress (t=0.05, p=.957), and self-efficacy (t=0.35, p=.726) in either group before and after the intervention. No intergroup differences were observed for psychosocial adaptation (t=0.12, p=.902), post-traumatic stress symptoms (t=0.07, p=.946), cultural adaptation stress (t=0.01, p=.994), and self-efficacy (t=0.58, p=.570). Conclusion These findings suggest that psychosocial adaptation, stress, and self-efficacy cannot be improved by a short-term intervention program alone. It was also determined that the cultural characteristics of the North Korean adolescent defectors were not sufficiently considered before implementing the program. Therefore, it is essential to provide an in-depth orientation for the participants before implementing the program.